Otra arquitectura Argentina : un camino alternativo - Gutiérrez, Ramón; Martín, Marcelo; Petrina, Alberto (Bogotá : Escal, 1989)
Década del 80
Keywords: ARQUITECTURA; ARGENTINA; SIGLO XX; MODERNIDAD; PALERMO